Simulation Effect Evaluation of CMIP6 Models on Climatic Elements in Huai River Basin - WU Chen; WANG Jingcai; SHAO Junbo; LI Xiangyu; WANG Wenyue (Renmin Zhujiang)
The general climate model (CMIP6) is the main means of large-scale simulation and prediction of future climate changes,but the simulation quality of its model data and applicability in different research regions need to be evaluated.Based on the measured data of 19 meteorological stations in the upper and middle reaches of the Huai River Basin from 1960 to 2014,this paper systematically evaluates the simulated climate data of 19 CMIP6 models using five precision indicators.The indicators include equidistant cumulative distribution function method,mean,dispersion coefficient (Cv),Pearson correlation coefficient (PCC),standard deviation (STD),and root-mean-square deviation (RMSE).Finally,the following conclusions are drawn:① Based on the simulation data of 19 CMIP6 models corrected for bias,the top two climate models for precipitation data simulation are preliminarily selected,including ACCESS-ESM1-5 and CMCC-ESM2.The top five climate models for simulating temperature data contain ACCESS-ESM1-5 and CMCC-ESM2;② The historical period data and measured historical climate data of the selected CMIP6 models are evaluated from two aspects of annual change trend and spatial distribution.Then,the CMIP6 model suitable for the upper and middle reaches of the Huai River Basin is verified and selected;③ Based on analyzing the influence of atmospheric circulation factors on climate,AO has a good correlation with the climate data of the upper and middle reaches of the studied basin,and the correlation between the model and atmospheric circulation data is close to the actual situation.The comprehensive evaluation shows that the most suitable models for simulating the upper and middle reaches of the Huai River Basin are ACCESS-ESM1-5 and CMCC-ESM2.The systematic evaluation of CMIP6 model data simulating the upper and middle reaches of the Huai River Basin provides theoretical and technical references for the rational selection and utilization of CMIP6 datasets for the research on climate change factors in future scenarios of the basin.